Diseño metodológico de Benchmarking competitivo en el sector de las servitecas caso Duitama Boyacá (2021)
The project main goal of this was to design based a methodology on Competitive Benchmarking taking as reference the automotive technical services or servitecas of the city of Duitama-Boyacá; this Benchmarking is based on the comparison with direct external competitors, that is, it seeks to identify the processes and success factors of other companies in order to improve and make changes, allowing to identify weaknesses and strengths with respect to the competition, and thus establish practices based on the successful experiences already achieved by other organizations; the objective of this process is gather valuable information with the purpose of guiding the service bureaus towards continuous improvement and to provide updated information about the environment in which they operate. This project will present the based methodology on three phases: the phase first , is description of the processes developed by these centers will be made through the design and validation of a characterization sheet; the second phase, the competitive of analysis profile it was determined based the on KPI and the development the matrix of critical success factors (CSF), which will result the classification the servitecas according their competitive level; and in the third phase, the tool for the configuration of improvement actions in relation to customer service will be developed, which will be proposed according to the results obtained